GOALS AND OBJECTIVES OF TEACHING A FOREIGN LANGUAGE IN SECONDARY SCHOOL - Kobilov Zafarjon Zokirovich; Nasimova Sohiba Yaxyayevna (KONFERENSIYALAR, 2025)
Abstract.  The  practical  goal  of  teaching  a  foreign  language  at  school  is  to  form  the foundations  of  practical  knowledge  of  foreign  languages  in  students.  Achieving  the  goals  and solving  the  tasks  set  is  carried  out  with  the  help  of  various  teaching  aids,  acting  in  a  certain, methodically determined system.